Trends in obesity prevalence during early pregnancy in Gran Canaria, Spain, 1993 to 2022 - Inmaculada Bautista-Castaño; Helmut Schröder; Laura Molero Sala; Alicia Inmaculada Martín Martinez; Verónica Dávila-Batista; Luis Peña Quintana; Lluis Serra-Majem (Frontiers in Reproductive Health, 2026)
Introduction The global prevalence of obesity has increasingly affected women of reproductive age, leading to several adverse outcomes during pregnancy, childbirth, and for their newborns. The objective of this study was to estimate time trends in early pregnancy among women who delivered live births in Gran Canaria (Spain) from 1993 to 2022 with stratified analysis by age, educational level, and parity. Methods Data were obtained from 178,305 pregnant women who delivered at the Maternal & Child University Hospital of Gran Canaria (HUMIGC) between 1993 and 2022. The study period was divided into three intervals: 1993–2001, 2002–2010, and 2011–2022. Trends of early pregnancy obesity prevalence were examined globally and by educational level, age groups, and parity categories. Analysis was performed by multivariable logistic regression, adjusted for potential confounder variables. Results The prevalence of obesity in early pregnancy increased significantly from 8.3% (95% CI 8.0–9.0) in 1993 to 22.5% (95% CI 21.0–24.0) in 2022. Multivariable logistic regression analysis adjusted for age, educational level, and parity revealed that obesity increased significantly in 2002–2010 (OR 1.73. 95% CI: 1.67–1.95) and further in 2011–2022 (OR 2.59, 95% CI 2.50–2.69) compared to 1993–2001. This upward trend was observed across all age groups, educational levels, and parity categories. Formal interaction analyses showed that the increase over time differed significantly according to age, educational level, and parity (all p for interaction < 0.001), with the greatest increases among women with university education and primiparous women. Conclusions The prevalence of obesity during early pregnancy significantly increased in Gran Canaria (Spain) between 1993 and 2022. This increase was consistent across age groups, educational levels, and parity categories. Prenatal counselling should be implemented to help overweight women lose weight before pregnancy, ensuring they are fully informed about the potential risk of excess weight on pregnancy, childbirth, and neonatal outcomes.